(untitled) (diségno, 2024)
Between 19 and 24 June 2023 in Brixen-Bressanone, the UIDSS2023, UID PhD Summer School was held, which, as every year, the Scientific Technical Committee funds by supporting the higher education of ICAR17 PhD students nationwide (fig.1). Participation in UIDSS2023 was possible following applications in response to a call for applications, and followed criteria based on plurality, rotation and the promotion of the participation of small and medium-sized sites. The number of applications exceeded 40 compared to the available places, which were 15 financed by the UID and 10 self-financed by the campuses, and PhD students of the XXXVI, XXXVII and XXXVIII cycles from 14 different universities (University of Bergamo, Cagliari, Catania, Chieti-Pescara, Florence, Genoa, Perugia, Pisa, Roma Tre, Roma Sapienza, Napoli ‘Federico II’, Sassari and the Politecnico di Milano e di Torino) participated. [read more]